1972
DOI: 10.1044/jshr.1501.179
|View full text |Cite
|
Sign up to set email alerts
|

Oral Vibrotactile Sensation: An Evaluation of Normal and Defective Speakers

Abstract: This investigation was concerned with testing for threshold responses to oral and nonoral region vibrotactile stimulation between a group of normal-speaking adults and a group with “functional” articulation speech defects. The findings were interpreted to mean that there was a consistent difference between groups with respect to oral vibrotactile sensitivity, but not with respect to nonoral vibrotactile sensitivity. The speech-defective group demonstrated less sensitive oral vibrotactile thresholds than those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

1972
1972
1988
1988

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Agreement among the studies as to the effect of vibration frequency has often been lacking. Supporting Verrillo's finding of a flat threshold function was an experiment reported by Fucci (1972) that compared the sensitivities of the tongue, palm, and lip when a rigid surround was used. The sensitivity of both oral structures remained constant between 60 and 900 Hz.…”
Section: Barry G Green Monell Chemical Senses Center Philadelphia mentioning
confidence: 68%
See 1 more Smart Citation
“…Agreement among the studies as to the effect of vibration frequency has often been lacking. Supporting Verrillo's finding of a flat threshold function was an experiment reported by Fucci (1972) that compared the sensitivities of the tongue, palm, and lip when a rigid surround was used. The sensitivity of both oral structures remained constant between 60 and 900 Hz.…”
Section: Barry G Green Monell Chemical Senses Center Philadelphia mentioning
confidence: 68%
“…This observation failed to explain why Fucci (1972) had originally obtained a flat threshold function while using the clamping procedure, or why Fucci and Petrosino (1982) found a very large (15-20 dB) effect of frequency on perceived intensity without using the clamping procedure. Clearly, the conditions under which frequency affects the sensitivity of the tongue to vibration have yet to be established.…”
mentioning
confidence: 67%
“…The apparatus used in the present experiment has been described in detail in a previous publication (Fucci, 1972). The stimulus unit included a sine wave generator, frequency counter, electronic switch (designed to maintain a sine wave configuration), interval timer, amplifier, variable attenuator, and electromagnetic vibrator.…”
Section: Methonmentioning
confidence: 99%
“…In comparing the vibrotactile thresholds obtained from the lip and tongue, Fucci (1972) reported that speech-defective Ss were less sensitive to vibrotactile stimulation than were unaffected speakers. The implication of this study suggested that poor oral vibrotactile sensitivity represented an interruption of the sensory control unit necessary for proper coordination of the articulators.…”
mentioning
confidence: 99%
“…Continuous closed -loop tracking of speech sounds is not only reflected in the sound patterns of speech , but also related to specific somesthetic processes associated with normal articulatory movements (Smith & Henry, 1967). Fucci (1972) reported differences between normal speaking and "functional" speech-defective adults when comparing vibrotactile thresholds obtained from the lip and tongue. Speech-defective Ss were found to be less sensitive for oral vibrotactile stimulation than unaffected speakers.…”
mentioning
confidence: 99%